2012
DOI: 10.1021/jp3034837
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of Prion Misfolding: Insights from Constant-pH Molecular Dynamics Simulations

Abstract: The prion protein (PrP) is the cause of a group of diseases known as transmissible spongiform encephalopathies (TSEs). Creutzfeldt-Jakob disease and bovine spongiform encephalopathy are examples of TSEs. Although the normal form of PrP (PrP(C)) is monomeric and soluble, it can misfold into a pathogenic form (PrP(Sc)) that has a high content of β-structure and can aggregate forming amyloid fibrils. The mechanism of conversion of PrP(C) into PrP(Sc) is not known but different triggers have been proposed. It can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 71 publications
0
48
0
Order By: Relevance
“…Using the PB-based DpHMD method [12], the Baptista and Machuqueiro groups investigated the pH-dependent conformational change of the prion protein [45, 46] as well as small peptides [47]. Using the GB-based DpHMD method [14], the Roitberg group studied the pH-dependent conformational variability of the Nitrophorin proteins [48, 49].…”
Section: Recent Applications Of Constant Ph Molecular Dynamicsmentioning
confidence: 99%
“…Using the PB-based DpHMD method [12], the Baptista and Machuqueiro groups investigated the pH-dependent conformational change of the prion protein [45, 46] as well as small peptides [47]. Using the GB-based DpHMD method [14], the Roitberg group studied the pH-dependent conformational variability of the Nitrophorin proteins [48, 49].…”
Section: Recent Applications Of Constant Ph Molecular Dynamicsmentioning
confidence: 99%
“…The results obtained for their studies in a diversity of biomolecular systems reveal the vast possibilities of the method. Examples include investigation on the pH-dependent conformational states of the analgesic dipeptide kyotorphin (L-Tyr-L-Arg) (Machuqueiro and Baptista 2007), the possibility of a trigged pH action on the misfolding of the prion protein into a pathogenic β-rich form (Campos et al 2010), the pH effects on the reversibility of prion misfolding (Vila-Viçosa et al 2012), a pH titration of all constituent lipids of a 25% DMPA/DMPC bilayer membrane model (Santos et al 2015), and the tight coupling between protonation and conformation for cytochrome c oxidase (Oliveira et al 2016).…”
Section: Other Common Constant Ph Simulation Methodsmentioning
confidence: 99%
“…It is well known that transition from PrP C to PrP Sc can be induced by infectious PrP Sc , or an external factor, such as low pH [1,2,34]. Many MD simulations have demonstrated the role of pH.…”
Section: Simulations In Prion Diseasesmentioning
confidence: 99%
“…They found that glycosylation could indeed stabilize the prion protein, indirectly through reducing the mobility of the surrounding solvents. Recently, several research teams have observed that the low pH-induced PrP transition could possibly be reversible, both in experiments and MD simulations [34,40,41]. Even in the strongly acidic environment of pH ¼ 1.7, the misfolding process could be reversed.…”
Section: Besides Infectious Prpmentioning
confidence: 99%